Analisis Penerapan Strategi Pemasaran Digital pada Bisnis Kecantikan Avoskin - Eka Permata Putri, Tyas; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
The beauty industry has undergone a remarkable transformation due to digitalization. As technology advances, the use of the internet and social media has changed consumer behavior and the way companies conduct their business. Digital marketing has become crucial for reaching the right market, increasing sales, and making profits, including in the beauty industry. This study aims to analyze the implementation of digital marketing strategies in the beauty business of Avoskin, focusing on influencer marketing and social media marketing. The method used is a literature study with a review of the literature on digital marketing, influencer marketing, and social media marketing. The discussion of this research identifies the advantages and disadvantages of these two strategies, as well as how their application strengthens brand awareness, increases engagement, and sales. The conclusion of this study shows that these two digital marketing strategies are very effective but require adjustments to overcome challenges such as algorithm changes and dependence on influencers. Digital marketing proves to provide great opportunities to build closer relationships with consumers but needs to be balanced with continuous innovation.